La frugalité contre l’extractivisme ? - Antoine Hardy; Arnaud Saint-Martin; Dana Diminescu (Socio, 2023)
Trying to conceptualize frugality in scientific life, and the many concepts that seem close to it, requires to understand the origins of this attempt to morally restore capitalism. The promises of frugal innovation renew the belief that tinkering with the rules of the market provides an answer to social problems, a variation on the old technicist promise, this time in a low-tech version, but without invalidating its limits and ambivalences. If the term frugality is not facing an attempt to put it on the agenda in the scientific field, its presence is inferred from a certain number of developments that are based on the idea that it would be possible to do better or the same with less. This constrained frugality can also be read as something that will limit or hinder the extractivism that can characterise, in very different contexts, scientific work and the relationship to knowledge, and can be understood as a form of “cultural poaching” in the sense given by Michel de Certeau (1990). This “frugal poaching” does not consist in a praise of resourcefulness within the limits of the current functioning of research but seeks to inventory the possibility of alternatives already present, without denying their contrasting effects.